Associations of kidney tests at medical facilities and health checkups with incidence of end-stage kidney disease: a retrospective cohort study - Ryuichi Yoshimura; Ryohei Yamamoto; Maki Shinzawa; Rie Kataoka; Mina Ahn; Nami Ikeguchi; Natsuki Wakida; Hiroshi Toki; Toshiki Moriyama (Scientific Reports, 2021)
Abstract No study has assessed the association between no health checkup and end-stage kidney disease (ESKD). This retrospective cohort study, including 69,147 adults aged ≥ 40 years in Japan who were insured by the National Health Insurance and the Late-Stage Medical Care System for the Elderly, assessed the associations of kidney tests at medical facilities and health checkups with incident ESKD. The main exposure was the histories of kidney tests using dipstick urinalysis and/or serum creatinine measurement at medical facilities and checkups in the past year: “checkups,” “no kidney test (without checkup),” and “kidney tests (without checkup)” groups. During the median observational period of 5.0 years, ESKD was observed in 246 (0.8%) men and 124 (0.3%) women. The “no kidney test” group was associated with ESKD in men (adjusted subhazard ratio of “no kidney test” vs. “checkups”: 1.66 [95% confidence interval, 1.04–2.65], but not in women. Age-specific subgroup analyses identified the “no kidney test” group as a high-risk population of ESKD in elderly men (1.30 [0.70–2.41] and 2.72 [1.39–5.33] in men aged 40–74 and ≥ 75 years, respectively). Elderly men with no kidney test at medical facilities and no health checkup were at higher risk of ESKD.